Reingeniería de procesos de la empresa pública de Rastro Catamayo, de la provincia de Loja - Celi García, Junior Ramón (2015)
This work is made on the basis of compliance with both the general objective and the specific; refriéndose first the general objective referred to Process Reengineering Public Company Catamayo Trail of the Province of Loja, in order to improve production processes that leads the company today. Importantly for the development of research work different methods and techniques that allowed gather important information about the current situation of the company, such as we were used: deductive, inductive, Analytical, descriptive and statistical; Techniques such as observation, Literature Review, Interview and Survey Manager for operational and administrative staff. So also for the development of this study it began with the collection of bibliographic information that enabled form a theoretical and conceptual support to scientific research framework. Following a situational analysis of the Public Utility Trail Catamayo, of which became evident that the company exists since 2011 as a public entity was made, is divided into two departments in which they work 12 employees, whose principal activity is the provision of slaughter. To obtain information about the operation of the company a survey of 12 workers and an interview with the Manager, instruments that allow the current situation of the processes that manage the company, showing the loss of time in some of them was applied. We identified each of the key processes of the company, when it is: Entry Animal Slaughtering Cattle, Hog Slaughtering, Billing and Collection, and finally deboning and Dispatch; subsequently redesign each process, bringing savings of time and resources for the company and in turn allowing better serve customers. Finally, conclusions and recommendations were established, with which it was determined that the reengineering project is desirable and should be executed, as it will bring a savings of $ 4,830.80 the first year because it will improve execution times in each of the processes and thus increase business productivity